Effectoffeeding low protein, glycine supplemented dietson growth performance of male and female broilers under the hot and humid tropical condition - Mohamed, Elmutaz Atta Awad; Idrus, Zulkifli; Farjam, Abdoreza Soleimani; Loh, Teck Chwen (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
The current study was conducted to investigate the influence of glycine (Gly) fortification to low crude protein (CP), essential amino acids (AA) supplemented diets on the growth performance of male and female broiler chickens under tropical hot and humid environment. In total, 800 day-old male and female broiler chicks were randomly divided into 50 floor pens of 16 birds each in a conventional open-sided house, and fed on 1 of 5 diets from 1 to 42 d of age (2 genders X 5 diets X 5 replicate pens X 16 birds per pen).In both genders, Gly fortification to the low-CP diets failed to support weight gain (WG) and feed intake (FI) equal to the PC group during the starter and the overall experimental periods. However, in females as well as the males with the highest supplemental Gly level, and except the group fed the NC diet, Gly fortification resulted in WG did not significantly differ from the group fed PC diet during the grower period. During all periods in males, and during grower and overall experimental periods in females, Gly fortification to NC diet with concentrations higher than NRC (1994) recommendations resulted in overall feed conversion ratio (FCR) equal to PC group in both genders.